Impact of fungicides and weather on cyclodepsipeptide‐producing Fusarium spp. and beauvericin and enniatin levels in wheat grains. (20th July 2018) - Decleer, Marlies; Landschoot, Sofie; De Saeger, Sarah; Rajkovic, Andrea; Audenaert, Kris
Abstract: BACKGROUND: Fusarium head blight (FHB) is a well‐known disease of wheat caused by a complex of Fusarium species. In this research, an extensive study on the occurrence of the emerging Fusarium cyclodepsipeptide mycotoxins beauvericin and enniatins was conducted in Belgian wheat grains harvested in 2015 and 2016. To assess the link between Fusarium species and their mycotoxin production, ultra‐performance liquid chromatography–tandem mass spectrometry was used to quantify the cyclodepsipeptide mycotoxins, while quantitative polymerase chain reaction was applied to quantify the presence of Fusarium species. RESULTS: It was shown that enniatins were mainly associated with the presence of F. avenaceum, while beauvericin, despite its low incidence, correlated significantly with F. poae . The application of fungicides resulted in a species shift and in the occurring mycotoxins. Concerning the effect of weather conditions, it was seen that levels of enniatins were positively correlated with the rainfall in May and June, while a negative correlation was observed with rainfall in the first half of July. CONCLUSION: Our study provides new insights into the occurrence of the emerging cyclodepsipeptide mycotoxins in an agro‐ecosystem in which fungicides are the main control measure against FHB. It seems that beauvericin and enniatin levels are affected by different parameters and behave differently upon application of fungicides. © 2018 Society of Chemical Industry